If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4 = 3x + 12 Reorder the terms: -4 + 2x = 3x + 12 Reorder the terms: -4 + 2x = 12 + 3x Solving -4 + 2x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -4 + 2x + -3x = 12 + 3x + -3x Combine like terms: 2x + -3x = -1x -4 + -1x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 -4 + -1x = 12 + 0 -4 + -1x = 12 Add '4' to each side of the equation. -4 + 4 + -1x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 12 + 4 -1x = 12 + 4 Combine like terms: 12 + 4 = 16 -1x = 16 Divide each side by '-1'. x = -16 Simplifying x = -16
| .06+.04x=18+.02 | | 8(b+7)=0 | | y=-4*-4+2*-4-7 | | 36y^7+4y^4= | | 4.5/g+2=3/0.5g-1 | | 12-5+x=5+8-2 | | 8x+2y+2=180 | | (2x+7)=87 | | 5d-4(d-9)=3d-(9-d) | | 3.5t+8=2.25t-16 | | 0.92x+.98(12-x)=.96(12) | | 3x^2-12x+165=180 | | y=-5*5+2*-3-7 | | 9n=3(n-2) | | 3x^2-12+165=180 | | 1-4x+4x^2=0 | | 2(3y-1)=-4 | | f=1.8x-11+32 | | F(9)=8 | | 3=3+-0.6 | | u^2-19u+90=0 | | X+30+63=180 | | 9a-25= | | 3x+15=2x-9 | | 5(b-4)=5b-2 | | 7y-4=7y+6 | | 0=3+-0.6 | | 28-x=-6(x-5)+5x | | 24=-8k-6k | | w+4W+12=13W+9 | | 6x-17x-28=0 | | 4c^2-1= |